The effect of kurut wood (Dysoxylum parasiticum) and jackfruit wood (Artocarpus heterophyllus) on the natural fermentation of palm juice and palm sugar quality - Siti Hikmatul Asyura; Syamsul Bahri; Dewa Ayu Citra Rasmi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aims to determine the effect of the concentration of kurut wood and jackfruit wood on the yield, pH, and percentage of reducing sugars of palm sugar. This experiment used a completely randomized design (CRD) which consists of 6 treatments, i.e., 0 g/L, 3 g/L, 4 g/L, 5 g/L, 6 g/L, and 7 g/L. The data were analyzed by Analysis of Variance (ANOVA) using Co-Stat software and posthoc analysis for chemical score using Orthogonal Polynomial Method (MOP). Statistical analysis of chemical value shows that the increase in the concentration of kurut wood and jackfruit wood (0 g/L – 7 g/L) significantly affects the decrease of the total microbe and percentage of reducing sugars, and the increase of the amount of yield, palm juice, and sugar pH. The 7 g/L treatment was the best, with different analysis results for kurut wood and jackfruit wood. In kurut wood, the total microbes counted 5.46 CFU/ml; yield 495.33g; pH 6.72; and reducing sugar 0.96. In jackfruit wood, total microbes counted 5.6 CFU/ml; yield 386.33g; pH 6.68; and reducing sugar 0.85.